Investigating the capacity of the cities to manage urban flooding disasters: a case study of Sumbe, Angola - Lemos de Lopes, Ngoia Cidalia (Department of Environmental and Geographical Science, 2025)
Disasters involving urban floods are a major concern worldwide, particularly in developing nations with limited capacity to manage disasters. Located on the coast of Angola and the capital of the Cuanza-Sul province in the central region of the country, Sumbe has been suffering from the negative impact of urban flooding, which has become more severe over the past five years. The purpose of this study was to investigate the capacity of the Sumbe municipality to manage urban flooding disasters, focusing on two distinct communities: Assaca and Centralidade da kibaúla. With the intent to assess the City's unique challenges, this case study used qualitative methods, involving 16 key stakeholders, 2 local officials and 7 community members from Assaca and Kibaúla. Findings revealed shortcomings in infrastructure, legal frameworks, early warning systems, preparedness, response, and recovery efforts in Sumbe. While both communities, Assaca and Centralidade da Kibaúla, face comparable challenges, there were some differences in socio-economic status influencing their capacity to respond effectively. This research provides insights in order to enhance disaster preparedness as well as mitigation endeavours in similar urban contexts.